Encouraging Community Action Against Teacher Absenteeism: A Mass Media Experiment in Rural Uganda. Issue 5 (4th May 2022) - Wilke, Anna M.; Green, Donald P.; Tan, Benjamin
Abstract: Chronic teacher absenteeism is widespread in Uganda, with approximately one-third of public school teachers absent on any given day. Absenteeism and other problems that arise in Uganda's public education system are often attributed to a lack of public oversight and parental involvement. In an effort to develop a scalable method of encouraging community engagement on this issue, the present study assesses the extent to which entertainment-education videos increase willingness among Ugandans to take action against absenteeism. Working in collaboration with Ugandan screenwriters and local actors, we developed video dramatisations that depicted the problem of absenteeism and how parents mobilised to address it. We assess the persuasive effects of these dramatisations both under lab-like conditions, to gauge immediate effects, and in the field, to gauge effects two months and eight months after a placebo-controlled media campaign attended by over 10, 000 Ugandans in 112 villages. Although the persuasive effects are weaker in the field than the lab setting, the former remain substantial even after eight months. The demonstrated ability of entertainment-education to change public views on this issue sets the stage for policy experiments that test whether entertainment-education campaigns have downstream effects on absenteeism and public school performance more generally.